Breast cancer in adolescent and young adult Ivory coast women: epidemiological and clinical features and molecular subdivision - Aka, Edele Kacou; Horo, Apollinaire; Koffi, Abdoul; Fanny, Mohamed; Didi-Kouko, Coulibaly; Nda, Guy; Abouna, Alain; Kone, Mamourou (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: To describe the anatomy and clinical features and then determine the histological and molecular profile of Ivorian women under 40 years. Methods: This is a retrospective multi-centre study descriptive and analytic performed over a period of 20 months. It involved 76 women on 355 selected in the Ivoirian cancer registry. An additional immunohistochemical analysis to assess hormone receptors and HER overexpression in a single unit. Results: Adolescents and young adults represented 20.3% of women with breast cancer. The average age of women was 35 years. (∂=3.4 years, 95% CI=[2.6415 to 4.1785]). 15.8% of patients had a good socioeconomic level with a stable job, well paid and 28.9% had a university degree. The discovery circumstances were a breast nodule (53%) followed by locoregional complications (21%) and breast self-examination (20%). The consultation delay was less than three months in 34.2% of cases. 78% of cancers were diagnosed in stage II and III. The most common histological subtypes were respectively RP (+) / Her (-) (41%) followed by triple negative (30%). Conclusions: This study showed that 20,3% of women under 40 years. The most tumors were classified as stage II and III of tumors at diagnosis. the most common histologic subtypes are the Luminal A (41%) and triple-negative (30%). This disease is more aggressive with a poor prognosis in this age group.